2003
DOI: 10.1007/s00467-002-0978-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis-B virus associated nephropathies: a clinicopathological study in 14 children

Abstract: Hepatitis B virus (HBV)-associated glomerulonephritides have been increasingly reported, and the association between HBV and glomerulopathy is striking, especially in children. In this study, we investigated clinical and immunohistological features of HBV-associated glomerulonephritis in 14 children aged from 2.5 to 16 years (mean 10 years). The nephrotic syndrome was present in 9 (64%) and the nephritic syndrome in 8 children (57%). Five children had both nephrotic and nephritic syndrome together (35%). Renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…It may be observed that in the mild ascites group, urinary RBP was higher and eGFR was lower compared those in the control group (P<0.01), whereas urinary mAlb, serum urea and serum Cr exhibited no difference compared with the control group (P>0.05), confirming that urinary RBP is a sensitive indicator of early renal damage in liver cirrhosis with ascites. The pathological classification of renal damage during the course of liver cirrhosis is difficult to determine; hepatitis-related IgA nephropathy and glomerular sclerosis are fairly common (28). A previous study including 65 cases with proteinuria >0.5 g/day, microscopic hematuria or renal damage of unknown causes (serum creatinine >1.5 mg/dl) in patients with liver cirrhosis observed lesions of different degrees in glomerular and non-glomerular structures, including renal blood vessels, renal tubules and renal interstitial fibrosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…It may be observed that in the mild ascites group, urinary RBP was higher and eGFR was lower compared those in the control group (P<0.01), whereas urinary mAlb, serum urea and serum Cr exhibited no difference compared with the control group (P>0.05), confirming that urinary RBP is a sensitive indicator of early renal damage in liver cirrhosis with ascites. The pathological classification of renal damage during the course of liver cirrhosis is difficult to determine; hepatitis-related IgA nephropathy and glomerular sclerosis are fairly common (28). A previous study including 65 cases with proteinuria >0.5 g/day, microscopic hematuria or renal damage of unknown causes (serum creatinine >1.5 mg/dl) in patients with liver cirrhosis observed lesions of different degrees in glomerular and non-glomerular structures, including renal blood vessels, renal tubules and renal interstitial fibrosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…A case of a pediatric patient with HBV-associated IgAN treated with interferon alfa-2a and lamuvidine has been reported to achieve both clinical remission and marked decrease in HBV DNA titer. 18 A study in patients with HBeAg-negative chronic HBV infection showed that either peginterferon monotherapy or combination therapy with lamivudine was more effective than lamivudine monotherapy in reducing HBV DNA levels. 19 However, the addition of lamivudine to peginterferon in this study did not improve posttherapy response rates.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of HBV-related MN toward ESRD occurs in approximately 25%-35% of adults compared with a rate of ,5% in children (15). Spontaneous biopsy-proven histologic resolution of MN has been shown in children which has been associated with systemic HBeAg clearance by the age of 4 years (16).…”
Section: Membranous Nephropathymentioning
confidence: 99%